In their own words: mental health and quality of life of West African refugees in Nigeria. (2014)
Refugees are exposed to extreme stressors and are therefore at risk of mental health and social problems. Other issues refugees have to cope with include the loss of their country, culture, language, profession, family, friends, and future plans. Much of the studies that have been done on refugee mental health have not attempted to explain what these experiences mean to these individuals. Thus, this study provides explorative data on the mental health and quality of life of West African refugees living in Nigeria in order to understand their views and perspectives. This study carried out in 2010 employed qualitative methods; a total of four focus group discussions (FGDs) were conducted among adult male and female refugees purposively selected at the Oru Refugee Camp, Ogun State, Nigeria. Respondents described quality of life as a major determinant of mental health status. Most of the participants believed that women were more predisposed to mental ill health due to their sensitive emotional make-up. Factors identified by respondents as affecting mental health and quality of life among refugees included poverty, unemployment, physical health, housing and environment, discrimination, stigmatization, and insecurity. Refugees rated their mental health and quality of life as poor due to the aforementioned factors. Recommendations were made to the international community, national and local governments to invest more on education, provision of vocational and entrepreneurial skills as well as adequate housing in order to improve the mental health and quality of life of refugees.